A ETNICIDADE GREGA: UMA VISÃO A PARTIR DE XENOFONTE - Cardoso, Ciro Flamarion (PHOÎNIX, 2020)
This text studies one of the leveis of ancient Greek ethnicity by the means of investigating such concept as illustrated by Xenophon's Anabasis — a source strategic for just this kind of research because the Greek army whose adventures in Asia are described by the Athenian author comprised Helenes from different parts of the Greek world: in this case, the decision of what was to be considered Greek, as different from `Barbarian', would necessarily depend on criteria recognized by people from various regions of the Greek-speaking ancient world. Some theoretical issues on ethnicity are also discussed.